Cortical Thickness and Clinical Findings in Prescholar Children With Autism Spectrum Disorder - Lucibello, Simona; Bertè, Giovanna; Verdolotti, Tommaso; Lucignani, Martina; Napolitano, Antonio; D’Abronzo, Rosa; Cicala, Maria G.; Pede, Elisa; Chieffo, Daniela; Mariotti, Paolo; Colosimo, Cesare; Mercuri, Eugenio; et al. (Frontiers in Neuroscience, 2022)
The term of Autism Spectrum Disorder (ASD) includes a wide variability of clinical presentation and this clinical heterogeneity seems to reflect a multifactorial still unclear ethiopathogenesis, encompassing exposure to different genetic risk factors and susceptibility to environmental factors. Several studies and many theories recognize as mechanisms of autism a disruption of brain development and maturation time-course, suggesting the existence of common neurobiological substrates such as defective synaptic structure and aberrant brain connectivity. Focusing on both the structural brain magnetic resonance imaging in order to examine region-specific structural changes and quantify specific alterations in gray or white matter there has been an attempt to identify a “MRI biomarker”. Our efforts on this study was the measurement of cortical thickness in a selected well known group of pre-schoolers ASD and the application of correlations of cortical indexes obtained and clinical features to understand the underlying mechanism of symptoms and to support early clinical diagnosis. Our results confirm that newer brain MRI techniques integrated to clinical data can provide some useful information in defining the cerebral regions involved in ASD although large sample studies characterized by homogeneous analytical and multisite approaches are needed.